Enhanced angiogenesis in the 3D dynamic responsive implant for inguinal hernia repair ProFlor. Issue 8 (21st March 2021) - Amato, Giuseppe; Puleio, Roberto; Rodolico, Vito; Agrusa, Antonino; Calò, Pietro Giorgio; Di Buono, Giuseppe; Romano, Giorgio; Goetze, Thorsten
Abstract: Biologic response to hernia prostheses represents a continuous source of debate. Conventional hernia meshes, in their typical static, passive configuration have been used for decades to reinforce the herniated abdominal wall. These flat implants, mainly fixated with sutures or tacks, induce poor quality fibrotic ingrowth that shrinks the mesh. In groin hernia repair, flat meshes are applied in the delicate inguinal surrounding where uncontrolled development of a scar plate can impair movement and may incorporate the sensitive nerves crossing this area. Complications deriving from mesh fixation and nerve entrapment are frequent and unpleasant for patients. To remedy these problems, a multilamellar shaped 3D device with a dynamic responsive behavior has recently been developed to repair inguinal hernia. Its inherent dynamic compliance during inguinal movements has shown to induce enhanced biological response with ingrowth of newly formed connective tissue, muscle fibers, and nerves. The function of these highly specialized tissue structures is supported by the contextual development of newly formed arteries and veins. The scope of the study was to assess quantity and quality of vessels, which had ingrown in the 3D hernia device in the short‐term, medium‐term, and long‐term post‐implantation, in biopsy specimens gathered from inguinal hernia patients operated with the 3D device. Starting from an early stage, widespread angiogenesis was evident within the 3D structure. Arteries and veins increased in quantity showing progressive development until full maturation of all specific vascular components throughout the mid‐term, to long‐term, post‐implantation. High quality biologic ingrowth in hernia prosthetics needs an adequate vascular support. The broad network of mature arteries and veins evidenced herewith seems to confirm the enhanced biological features of the dynamic responsive 3D device whose features resemble a regenerative scaffold, an ideal feature for the treatment of the degenerative source of inguinal hernia disease. Abstract : Angiogenetic sequences in ProFlor starting from short term post implantation, along the mid term, until the long term. VEFG/α‐SMA ratio confirms the structural maturation of the neovessels.